The Canadian Distinctiveness into the XXIst Century - La distinction canadienne au tournant du XXIe siÃ¨cle - Gaffield, Chad (International Canadian Studies Series, 2003)
In this collection of essays some of Canada's foremost writers and thinkers, including John Ralston Saul and Margaret Atwood, call for equilibrium among economics, culture, and technological change. While promoting the dynamism and change possible in Canadian society, they also call for a re-examination of Canada's past in order to chart its future.